Response surface modeling and optimizing conditions for anthocyanins extraction from purple sweet potato (Ipomoea batatas (L.) Lam) grown in Lam Dong province, Vietnam - T. N., Pham; B. P., Tran; T. H., Tran; D. C., Nguyen; T. N. P., Nguyen; T. Q., Nguyen; D. V. N., Vo; N. T. H., Le; X. T., Le; T. D., Nguyen; L. G., Bach (Institute of Physics Publishing, 2019)
Anthocyanin is increasingly used as a natural and safe coloring agent. In this paper, the extraction of purple sweet potato anthocyanin (PSPAs) was investigated by using response surface methodology (RSM). Different extraction temperatures of solvent ethanol (60 - 70 °C), duration of extraction (35 - 45 min) and solid-liquid ratios (4:1 - 6:1) were selected in order to extract PSPAs. The highest anthocyanin content of 206.019 mg/L of PSPAs was collected at the solid liquid ratio 6:1, extraction time 39.61 min, and temperature 67.38°C. PSPAs yield detailed significant correlation with high F values, low P values (<0.0001), the determination coefficient (R2=0.9986) and a high desirability 93.5%.